Learning with mobile devices: A comparison of four mobile learning pilots in Africa - Shafika Isaacs; Nicky Roberts; Garth Spencer-Smith (South African Journal of Education, 2019)
This paper compares the mixed-methods evaluation findings of the ukuFUNda Virtual School (UVS) with evaluations of three different mobile learning (m-learning) programmes in Africa: the information and communication technologies for rural education (ICT4RED); the Kenya Primary Math and Reading (PRIMR) study and the Nokia Mobile Mathematics (MoMath) evaluation. The comparison applies a conceptual model based on m-learning affordances and configurations (Strigel & Pouezevara, 2012), as well as on uptake, use, and responses by program beneficiaries; and on stakeholder learning. The findings show varied successes across all four programs and highlight important lessons for stakeholders with particular reference to scaling up of m-learning interventions in an African context.